2018
DOI: 10.1016/j.isci.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Alters the Properties of Pol η: Implications for Translesion Synthesis

Abstract: SummaryThere are significant ambiguities regarding how DNA polymerase η is recruited to DNA lesion sites in stressed cells while avoiding normal replication forks in non-stressed cells. Even less is known about the mechanisms responsible for Pol η-induced mutations in cancer genomes. We show that there are two safeguards to prevent Pol η from adventitious participation in normal DNA replication. These include sequestration by a partner protein and low basal activity. Upon cellular UV irradiation, phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…In line with our finding that Cdc28 -dependent phosphorylation was important for Polη function in response to damage, phosphorylation of human Polη after UV irradiation is required for localization to sites of lesions, and contributes to cell survival after UV exposure ( Chen et al 2008 ; Bertoletti et al 2017 ; Peddu et al 2018 ). As opposed to the human counterpart, however, nuclear accumulation of yeast Polη seems to be independent of the DNA damage response, since WT Polη and the Polη-S14A mutant both accumulated in the nucleus in the absence of break induction, and were insensitive to UV irradiation ( Figures 2B and 5B and Figure S3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our finding that Cdc28 -dependent phosphorylation was important for Polη function in response to damage, phosphorylation of human Polη after UV irradiation is required for localization to sites of lesions, and contributes to cell survival after UV exposure ( Chen et al 2008 ; Bertoletti et al 2017 ; Peddu et al 2018 ). As opposed to the human counterpart, however, nuclear accumulation of yeast Polη seems to be independent of the DNA damage response, since WT Polη and the Polη-S14A mutant both accumulated in the nucleus in the absence of break induction, and were insensitive to UV irradiation ( Figures 2B and 5B and Figure S3).…”
Section: Discussionsupporting
confidence: 89%
“…Polη ubiquitination, for example, restricts its accessibility to replication forks ( Cipolla et al 2019 ). In addition, phosphorylation of human Polη is required for its localization to sites of UV-induced DNA lesions ( Chen et al 2008 ; Bertoletti et al 2017 ; Peddu et al 2018 ). These findings prompted us to investigate whether Polη would be regulated through post-translational modification(s) also for formation of damage-induced cohesion.…”
mentioning
confidence: 99%
“…This process is required for cell survival following UV exposure and thereby provides an association between UV‐induced cell cycle arrest and TLS. Another study was performed by Peddu et al (2018) and they shown that phosphorylation of Pol η increases its affinity for ub‐PCNA, and thus impacts TLS regulation. They also demonstrated that, PDIP38 sequestered the Pol η away from the replication machinery, and prevents it from interfering with high fidelity polymerases in normal cells.…”
Section: Pol η Escalating Tlsmentioning
confidence: 99%
“…Although PrimPol is required for replication fork progression under both normal and DNA-damaging conditions (40), the mutual exclusivity of PCNA/PrimPol binding to PCNA could help prevent aberrant PrimPol recruitment to the replication fork when PCNA is in complex with Pold. POLDIP2 has been reported to be phosphorylated on Ser 147 and Ser 150 by the ATR kinase following UV irradiation (36). These two serine residues are found immediately beside PIP2 ( Figure 1) and with phosphorylation adding bulky negatively charged groups, the binding properties of PIP2 would likely be changed.…”
Section: Structural Insights Into Poldip2 Interactions With Primpolmentioning
confidence: 99%